2013
DOI: 10.1007/s10195-013-0253-z
|View full text |Cite
|
Sign up to set email alerts
|

Peri-articular diseases of the hip: emerging frontiers in arthroscopic and endoscopic treatments

Abstract: The precise diagnosis of both intra and extra-capsular disease of the hip is now possible because of commonly available advanced diagnostic imaging techniques. An increasing number of reports in the orthopedic literature describe new endoscopic and arthroscopic techniques to address peri-articular pathology of the hip. The purpose of this paper is to review current techniques in the management of extra-articular hip conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 60 publications
0
16
0
2
Order By: Relevance
“…The authors have recently reported of a cyst in the medial synovial fold abutting against the zona orbicularis, which led to pectineofoveal impingement in a 13-year-old girl who presented with hip pain and clicking which had been affecting her for over six months. After the cyst was detected and removed arthroscopically, she was asymptomatic and remains active with no clicking or pain at the last follow-up [67].…”
Section: Aetiology and Clinical Featuresmentioning
confidence: 94%
See 1 more Smart Citation
“…The authors have recently reported of a cyst in the medial synovial fold abutting against the zona orbicularis, which led to pectineofoveal impingement in a 13-year-old girl who presented with hip pain and clicking which had been affecting her for over six months. After the cyst was detected and removed arthroscopically, she was asymptomatic and remains active with no clicking or pain at the last follow-up [67].…”
Section: Aetiology and Clinical Featuresmentioning
confidence: 94%
“…Pectine-ofoveal impingement is a rare condition, which can cause unexplained hip or groin pain in young adults, and only two articles describing this pathology have been published thus far [66,67]. The medial synovial fold represents a fibrous band located anteromedially on the femoral neck, and it is consistently visualised during arthroscopy of the peripheral compartment of the hip.…”
Section: Pectineo-foveal Impingement Anatomical Considerationsmentioning
confidence: 99%
“…45 Arthroscopic iliopsoas release appears to be successful and in case series there are higher success rates and less recurrence with the endoscopic technique compared with open procedures. 46 External snapping of the hip can be operated endoscopically when conservative treatments fails. An endoscopic iliotibial band Z-or diamond-shaped release is performed.…”
Section: Results In Extra-articular Lesionsmentioning
confidence: 99%
“…43 Peri-articular hip diseases, which are possible to address endoscopically, can be divided according to anatomical compartments involved. 44 • Anterior to the hip joint: internal snapping hip syndrome, psoas tendon impingement, rectus femoris rupture or avulsion fracture and antero-inferior iliac spine impingement.…”
Section: Extra-articular Lesionsmentioning
confidence: 99%
“…1,2,13 Current endoscopic procedures performed in the periarticular space include correction of anterior inferior iliac spine impingement, ischiofemoral impingement, 4 bursal resection, reattachment of gluteal tendons, proximal hamstring tendon repair, 16,21,22 and sciatic nerve release. 1,2,13,16,22 The increased implementation of extra-articular hip endoscopy demands more accurate recognition of landmarks on radiographs. While research has addressed the applications of periarticular endoscopy 1,2,13 and the anatomy of the proximal femur, 22 there is a lack of an established and validated radiographic description of the surgical landmarks of the proximal femur.…”
mentioning
confidence: 99%